Is terminology the real problem in failure to implement STEM Education in African languages? Translanguaging as an intervention strategy - Nhongo, Raphael; Tshotsho, Baba Primrose (2022)
English has remained as the sole language of instruction for science, technology, engineering and mathematics (STEM) subjects in Anglophone African countries. The use of English as the only medium in the teaching and learning of STEM subjects has been based on the fact that African languages lack requisite terminology. The paper seeks to answer the questions: •To what extent are the inadequacies in African languages terminology hindering the teaching of STEM subjects in these languages? •Is lack or inadequacy in terminology, the real reason for excluding African languages in the teaching and learning of STEM subjects? •What options can be adopted to achieve the inclusion of African languages in the teaching of STEM subjects? To answer these questions, the study took a phenomenological qualitative research design which was complemented by textual analysis to interrogate the exclusion of African languages in the teaching of STEM subjects. Semistructured interviews with 20 teachers of STEM subjects were conducted in Bulawayo, Zimbabwe. The results of the study revealed that while teachers and linguists are aware that the inclusion of the learners’ first languages in the teaching of STEM subjects have cognitive benefits, perceived inadequacy in African languages terminologies and fear of isolation remain as hindrances.The study reflected that if African languages in STEM education are included through translanguaging the fears of isolationand misconceptions of inadequacies in terminologies would be conquered.The paper concludes that lack or inadequacy in terminologies in African languages is not a problem but what is the problem is that the inclusion of African languages in the teaching of STEM subjects has been interpreted as a move to totally dislodge English language. African languages and English can be used together in the teaching of STEM subjects through translanguaging.